2012
DOI: 10.3800/pbr.7.41
|View full text |Cite
|
Sign up to set email alerts
|

Vertical distribution and seasonal variation of pelagic chaetognaths in Sagami Bay, central Japan

Abstract: Abstract:The vertical distribution and seasonal variation of pelagic chaetognaths was investigated in Sagami Bay, based on stratified zooplankton samples from the upper 1,400 m. The chaetognaths were most abundant in the 100-150 m layer in January and May 2005, whereas they were concentrated in the upper 50 m in the other months. Among the 28 species identified, Zonosagitta nagae had the highest mean standing stock, followed by Flaccisagitta enflata and Eukrohnia hamata. Cluster analysis based on species compo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2013
2013
2023
2023

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 10 publications
(4 citation statements)
references
References 38 publications
0
4
0
Order By: Relevance
“…Z. nagae in May and June, and S. pacifica in September. Miyamoto et al (2012) also studied species-specific vertical distributions of chaetognaths seven times in Sagami Bay and calculated the population mean depths, which they referred to as WMD (weighted mean depth). According to their results in Sagami Bay : table 1), the ranges of the population mean depths were 11-111 m (mean 46 m) in Z. nagae, 9-62 m (33 m) in F. enflata, 6-32 m (17 m) in A. regularis, and 15-135 m (71 m) in S. pacifica.…”
Section: Spatial Distributionmentioning
confidence: 99%
“…Z. nagae in May and June, and S. pacifica in September. Miyamoto et al (2012) also studied species-specific vertical distributions of chaetognaths seven times in Sagami Bay and calculated the population mean depths, which they referred to as WMD (weighted mean depth). According to their results in Sagami Bay : table 1), the ranges of the population mean depths were 11-111 m (mean 46 m) in Z. nagae, 9-62 m (33 m) in F. enflata, 6-32 m (17 m) in A. regularis, and 15-135 m (71 m) in S. pacifica.…”
Section: Spatial Distributionmentioning
confidence: 99%
“…Miyamoto et al. ( 17 ) investigated the vertical distribution of chaetognaths in Sagami Bay and reported that the mean depths were different between the two Krohnitta species (30 m and 194 m in K. pacifica and K. subtilis , respectively). In future, if highly precise depth information for the two species becomes available, then differences in thermal habitat between the two species may be detected more precisely.…”
Section: Discussionmentioning
confidence: 99%
“…BISMaL archived a total of 904 records of K. pacifica and 1136 records of K. subtilis during 1982–1992, and there were no in situ temperature data for the two species. The two Krohnitta species are both categorized as epiplanktonic (>150 m) species ( 15 ), but K. subtilis has also been reported as mesopelagic in the eastern area of Japan ( 16 ) and Sagami Bay ( 17 ). As the depth data for all observation records of the two species were reported as ranges (mostly 0–200 m), BISMaL used a depth of 0 m for the estimation.…”
Section: Methodsmentioning
confidence: 99%
“…Zonosagitta nagae (Alvariño, 1967) is a dominant chaetognath species in the zooplankton community in warm waters around Japanese coastal areas (Marumo and Nagasawa 1973, Itoh et al 2006, Miyamoto et al 2012, Ohnishi et al 2014. This species is particularly abundant in surface waters from spring to summer and predominantly preys on copepods and a variety of other organisms including fish larvae in the field (Nagasawa and Marumo 1972, 1976, Terazaki 2005.…”
Section: Introductionmentioning
confidence: 99%